Chromatic characteristics and color-related phenolic composition of Brazilian young red wines made from the hybrid grape cultivar BRS Violeta (BRS Rúbea×IAC 1398-21) - Lago Vanzela, Ellen Silva [UNESP]; Rebello, Ligia Portugal Gomes; Ramos, Afonso Mota; Stringheta, Paulo César; Da-Silva, Roberto [UNESP]; García-Romero, Esteban; Gómez-Alonso, Sergio; Hermosín-Gutiérrez, Isidro (Elsevier, 2013)
The color characteristics and the phenolic composition related to color of young red wines elaborated with the hybrid grape cultivar BRS Violeta, developed for its adaptation to sub-tropical climates in Brazil, have been studied. These wines are characterized with a deep red-purplish color, reaching color intensity averaging 24 units. In spite of being young red wines elaborated with short maceration time, their content in total polyphenols was very high (around 3692. mg/L, as gallic acid equivalents), especially when compared to similar Vitis vinifera young red wines. Within polyphenols, anthocyanins predominated (around 2037. mg/L, as malvidin 3,5-diglucoside equivalents) and they were almost exclusively anthocyanidin 3,5-glucosides (ca. 97%), mainly built from B-ring tri-substituted anthocyanidins (delphinidin. >. petunidin. ≈. malvidin) and having high proportion of p-coumaroylated derivatives (ca. 28%) that confer higher stability. The content of hydroxycinnamic acid derivatives was also remarkable (ca. 95. mg/L, as caffeic acid equivalents) and unknown glucose derivatives of p-coumaric acid accounted for ca. 42% of total HCAD. Finally, these found flavonols were mainly based on myricetin whereas kaempferol derivatives were missing, their total content being within the ranges usually found for V. vinifera wines, but reaching their top values (ca. 91. mg/L, as quercetin 3-glucoside equivalents). All the aforementioned data suggest that Violeta wine could be considered an important dietary source of healthy polyphenols with a moderate alcoholic content (ca. 11.6%). © 2013 Elsevier Ltd.
Keywords: Anthocyanins; BRS Violeta; Flavonols; Hybrid grape; Hydroxycinnamic derivatives; Wine color; Color characteristics; Glucose derivatives; Hybrid grapes; Hydroxycinnamic acid derivatives; Phenolic composition; Carbohydrates; Color